Upsurge in the incidence of scabies (a neglected tropical disease) in some rural communities of Southeast Nigeria: any nexus with climate change? - Umegbolu, Emmanuel I. (International Journal Of Community Medicine And Public Health, 2021)
Background: Scabies is characterized by the presence of burrows, erythematous papules, and generalized pruritus which is usually worse at night. Recently an upsurge in the incidence of scabies has been reported in many settings, including the area of the study. The study aimed to determine if there is a nexus between scabies and climate change as a risk factor. Methods: This was a case-control study carried out in a Cottage Hospital. Case files of 18, 000 patients who attended the hospital between 2016 and 2019 were reviewed. The diagnosis was mainly clinical, i.e. based on the presence of itching in the typical scabies locations, presence of scabies burrows and history of similar itching in the other members of the patient’s household. 112 cases of scabies were diagnosed within this period. Results: From 2016 to 2019, the incidence of scabies rose from 3 to 50. Prevalence among males was 59.8%, and in females 40.2%, although the difference was not significant (p=0.0.53). Compared to other age groups, prevalence was highest in the 6-17 years age group (37.5%), but the difference among the age groups was also not significant (p=0.84). Conclusions: Within four years (2016-2019), the incidence of scabies had risen from 3 to 50 in the area of the study, being higher in males (59.8%) than females (40.2%), and in children less than 18 years (37.5%). Community survey, prompt diagnosis, adequate treatment and avoidance of overcrowding might help to stem the observed rising incidence of the disease.